Analysis of Predisposing Factors Related to Mothers With Toddler’s Visit to Integrated Community Health Service - Ernawati, Naya; C , Nadhya Sasadhara; Wulandari , Eka; Astuti , Erlina Suci; Solikhah, Fitriana Kurniasari; Ugsang Acob, Joel Rey (Tarqabin Nusantara Group, 2023)
Abstract Introduction: Mothers’ behavior has an important role in the growth and development of toddlers and affects the mothers’ visit frequency to integrated community health service. It is also affected by some aspects and various factors, one of which is predisposing factors. The purpose of this research was to identify predisposing factors related to mothers with toddlers’ visit to integrated community health service in Mojoroto sub-district, Kediri city. Method: The research used survey analytic method with a cross sectional design. The sample of this study was the whole population consisted of 40 mothers who had toddlers aged 0-59 months. Data collection was using a questionnaire. Data analysis was using univariate, bivariate with chi-square and Odds Ratio. Results: The results of this research showed that the mothers’ visit to integrated community health service had correlation with employment status factor (p value 0.024; OR 4.5), and the factors which did not have any correlation with the mothers’ visit were the knowledge (p value 0,385), attitude (p value 0,622), education (p value 0,057), motivation (p value 1,000), and the age (p value 0,251). It is recommended that those mothers must always be advised and encouraged to join integrated community health service activities to keep monitoring the growth and development of their toddlers by taking them to available health service centers. Keywords: predisposing factor, mothers’ visit, integrated community health service